Development of orgware of borrower - legal entity’s solvency analysis - Vygovska N.G.; Vygovskyy V.G. (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2017)
The article is devoted to the development of orgware of borrower - legal entity’s solvency analysis. The authors investigate the orgware of solvency estimation mechanism in two aspects: 1) as the aggregate of the organizational stages of solvency estimation; 2) as an organizational structure and co-operation between different structural subdivisions of bank. The paper itemizes and specifies the stages of orgware of borrower - legal entity’s solvency analysis according to such signs as the purpose of the stage; responsible for the stage; the issues studied on the stage; documenting, duration and features of the organizational stage). The documentary providing of the process organization of solvency analysis is improved, namely, the appendix to executive Summary «Estimation of off-balance sheet obligations (off-balance sheet risks) of borrower on the project credited» is offered. The authors’ attention is paid to the existence (in international practice) of two methods of organization process of enterprises-borrowers’ rating: 1) oriented to the external rating and 2) oriented to the internal rating, their advantages and disadvantages are identified. The article offers the algorithm of informative co-operation of basic subjects of borrower’s solvency analysis after the selected organizational stages at forming of the internal credit rating, which will be instrumental in the improvement of process of enterprises’ crediting, standardization of procedure, and decline of crediting risks.